H.264/AVC Video Steganography Techniques: An Overview - Dalal, Mukesh; Juneja, Mamta (International Journal of Computer Sciences and Engineering, 2025)
Video steganography is a process of embedding data inside in a raw or compressed video sequence. Nowadays compressed videos are preferred over raw videos for data transfer, and H.264/ AVC video format is the most frequently used video standard over the internet. H.264/AVC provides more compression as compared to the previous standards and maintains better visual quality. In H.264/ AVC video steganography the message hiding can be done by conventional methods such as spatial domain and transform domain techniques. Additionally, it has more hiding options as compared to the previous standards which are also utilized by researchers for secret data embedding. In this paper, a concise overview of H.264/ AVC video standard is given, and survey of existing video steganography techniques in H.264/ AVC is also done with the implementation of a 4-0-4 LSB technique to show the impact of embedding. The pros and cons of different hiding techniques used for data embedding in H.264/AVC video are discussed towards the end. This paper aims to provide a brief introduction of video steganography techniques in H.264/ AVC video coding standard.